Development of a carbamate-conjugated catechol ligand and its application to Cs extraction from contaminated soil by using supercritical CO2. (March 2020) - Park, Kwangheon; Kim, Taehun; Park, Jihey; Yan, Xinhao; Kim, Hakwon
Abstract: Extraction of radioactive Cs from contaminated soil is a crucial aspect of remediation after nuclear accidents. For this purpose, we have developed a new type of ligand, carbamate-conjugated catechol, to assist in metal extraction by using supercritical CO2 (SCCO2 ). The synthesis process for this ligand is relatively simple, and the carbamate-conjugated catechol ligand dissolves well in SCCO2 . The measured ligand distribution coefficient increased according to a power law with an exponent of 1.7 as the ligand concentration increased, indicating that approximately two ligand molecules are needed to extract one Cs ion. The roles of additives (ligand, co-ligand, and water) were limited when they were used separately, but the combination of these additives was important. We tested 27 combinations of these three additives for extracting Cs from artificially contaminated sea sand. A quantitative analysis indicated that the ligand had the strongest influence on Cs extraction, followed by water, and the co-ligand. The carbamate-conjugated catechol ligand was then used for Cs extraction from artificially contaminated real soil. Three types of soil were prepared: coarse soil (particle size = 0.5–1 mm), medium soil (particle size = 0.2–0.5 mm), and fine soil (particle size < 0.2 mm). The Cs fractions extracted from the coarse, medium, and fine soils were measured to be 95%, 91% and 70% of the Cs fraction extracted from sea sand, respectively, which indicates the existence of a surface area effect. Additionally, we suspect that Cs undergoes chemical interaction on the surface of real soil. Highlights: A catechol ligand was developed for the use of the metal extraction using supercritical CO2 . The catechol ligand successfully extracted Cs from artificially contaminated real soil. Approximately two molecules of the catechol ligand are needed to extract a Cs ion.